Hak Cipta Sebagai Collateral Dalam Jaminan Fidusia - Atikah, Ika (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2019)
This article is focusing for copyright objects that can be made collateral for loans that have economic values ​​according to get in fiduciary collateral. After Amendment Act No. 24/2002 became Act No. 28 / 2014 concerning copyright, it provided convenience for creators to be able to request credit collateral (collateral) and object of fiduciary collateral. The rules for copyright as collateral for credit are in accordance with the provisions in the contract, in accordance with the provisions in the imposition, registration and transfer of related Fiduciaries in Act No. 42/1999 concerning Fiduciary Guarantees. The Copyright Law also approves article 16 paragraph 3 of the creator to guarantee his work through fiduciary guarantees. It is possible to be able to politicize the results of his creation, it is the creator of copyrighted work that can improve the quality of creation. Key word : copyright, collateral, fiduciary